Influência da temperatura e da fluidodinâmca no desaguamento e secagem térmica de lodo de estação de tratamento de esgoto do tipo UASB utilizando energia solar e GLP - Gomes, Lorenzo Alfonso Caliari de Neves (2023)
The management of sewage sludge is a challenge for companies in the area because its management has a significant operational cost. Urban growth combined with new legislation and environmental policies required a change in the way of treating sewage sludge. Previously seen as waste from the sewage treatment process, today it is seen as an input in different applications, such as agriculture. The agricultural sector has room to receive a large part of this input. However, for the sludge to be used as an input, it must go through several stages in what is called sludge management, where, in the end, the sewage sludge becomes a biosolid. Among these steps, dewatering and drying stand out, as they are capable of significantly reducing the volume of sludge handled. These two processes are usually carried out in different locations and a logistical step is required to take the dewatered sludge to the drying process. Drying can be carried out by burning fossil fuels or by using solar energy. This work proposes the use of a greenhouse to carry out the dewatering and drying processes simultaneously. This unified process is carried out using solar energy as a primary source of energy and the burning of LPG as a secondary source. For this, a greenhouse was developed for drying in mixed mode, that is, with a solar collector heating the inlet air. A Class B biosolids, with solids content above 90%, was produced in 8 days. A CFD mathematical model was developed to evaluate and identify improvements in the developed greenhouse.